(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
As is known, copper-zinc ores are the most difficult for selective flotation. Difficulties are associated with the nature of zinc blende and changes in its floatability under the influence of processes occurring at the deposit, during grinding and during flotation.